Koncepcja mechanizmu funkcjonowania gospodarki socjalistycznej Oskara Lange z okresu międzywojennego - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1979)
The first developed vision of a mechanism of functioning socialist economy can foe met in Polish economic literature in O. Lange and M. Breiťs elaboration entailed "The Way to a Socialist Planned Economy" in 1934. The model solutions of the authors resulted not only from deep theoretical considerations but also from observation of the October Revolution and then the socialist construction of the Soviet Union in Lenin's period. O. Lange wrote then his treatise "On Economic Theory of a Socialist economy" provoked by radical oponents of socialism. It composed a reply both to L. von Mises' attacks and to positive proposals of principles of functioning a socialist economy. Socio-economic framework of O. Lange's model was close to the mechanism formulated in the year 1934. The differences concerned the basic scope of using a market mechanism. In the model from the years 1936 - 37 O. Lange renounced the assumption on existance of a production means market similar to the concumers' goods and labour markets. In his subsequent articles ("Essence of Socialism" and "What Socialism Means to Me") O. Lange developed some earlier formulations concerning essence of socialist system, its historical premisses and outlines of heterogenity, democratic forms of social life, autonomity etc. General outline of O. Lange's concept of optimizing mechanism of functioning socialist economy, elaborated in the period of developing political economy of socialism as a science, in spite of some weaknesses has to be considered as a great theoretical achievement. He proved that possibilities of rational economy are real only under conditions of socialist system, because that system naturally serves to realization of proper ideas of society's welfare.
On a Concept of Functioning Socialist Economy by O. Lange in the Period Between the Two World Wars